A novel cholesterol/lipid delivery system for murine myeloma cell lines. (7th March 2017) - Chauhan, Gaurav; Schmelzer, Albert E.
Abstract : Murine myeloma NS0 cells are cholesterol‐dependent auxotrophs and require externally provided cholesterol for sustained growth. Traditionally, cholesterol is provided to these cells by supplementing cell culture media with a concentrated solution of cholesterol and other water insoluble components dissolved in 200‐proof ethanol. However, the solubility of cholesterol in ethanol is limited, and for processes requiring large amounts of cholesterol, the consequential increase in added ethanol may negatively impact cell growth. Additionally, the flammability of 200‐proof ethanol may restrict the preparation scale and storage volumes at a large‐scale facility, thus resulting in a more complex preparation procedure due to safety guidelines. This study proposes 1‐propanol as an alternative solvent, which can dissolve up to 40 g L −1 of cholesterol along with other water insoluble components, as compared to ethanol, which can dissolve up to 10 g L −1 of the same. A concentrated formulation simplifies the preparation method and ameliorates the procedural and operational challenges, as well as reduces the total amount of alcohol added to a cell culture by ∼80% when compared to the ethanolic solution, to deliver the same amount of cholesterol, thereby significantly minimizing alcohol exposure to the cells and mitigating the fire hazards at a large‐scale facility. © 2017 American Institute of Chemical Engineers Biotechnol. Prog., 33:795–803, 2017